Using Conditional Percentages During Free-Operant Stimulus Preference Assessments to Predict the Effects of Preferred Items on Stereotypy: Preliminary Findings. (September 2015) - Frewing, Tyla M.; Rapp, John T.; Pastrana, Sarah J.
To date, researchers have not identified an efficient methodology for selecting items that will compete with automatically reinforced behavior. In the present study, we identified high preference, high stereotypy (HP-HS), high preference, low stereotypy (HP-LS), low preference, high stereotypy (LP-HS), and low preference, low stereotypy (LP-LS) items based on response allocation to items and engagement in stereotypy during one to three, 30-min free-operant competing stimulus assessments (CSAs). The results showed that access to HP-LS items decreased stereotypy for all four participants; however, the results for other items were only predictive for one participant. Reanalysis of the CSA results revealed that the HP-LS item was typically identified by (a) the combined results of the first 10 min of the three 30-min assessments or (b) the results of one 30-min assessment. The clinical implications for the use of this method, as well as future directions for research, are briefly discussed.